Mentorship, Misrepresentation, and Moving Forward: Reflections from a team of Métis Scholars in Indigenous Health Research - Hayward, Ashley; Cyr, Monica; Hallett, Charlene (Pawaatamihk)

(untitled) (University of Winnipeg, 2025)
In Indigenous health research, mentorship shapes career trajectories, influences relationships with communities, and creates opportunities for growth. This paper presents reflections from Métis scholars whose early careers were influenced by a mentor later alleged to have misrepresented their identity. We examine how this experience disrupted academic and community relationships, eroded trust, and required navigation of complex emotional and political contexts. Grounding our work in Métis ways of knowing, we highlight both the harms experienced and the resilience fostered through new kinship networks. We conclude by outlining strategies to rebuild trust, support Indigenous scholars, and advance Indigenous health research with integrity and care.